Exploring the linkages between energy, gender, and enterprise: Evidence from Tanzania. (April 2020) - Pueyo, Ana; Carreras, Marco; Ngoo, Gisela
Highlights: The paper provides evidence about gender differences in the productive use of energy. The research focuses on fishing communities in Lake Victoria, Tanzania. Men and women use different types and quantities of fuel in their enterprises. Electricity is consistently associated with better business performance. A multi-methods approach combining qualitative and quantitative research is used to gather evidence. Abstract: The productive use of electricity is essential for poverty reduction in newly electrified rural communities as well as for the financial sustainability of electricity suppliers. Because men and women assume different roles in the rural economy, the inclusion of gender concerns in interventions to promote productive uses of energy could improve development outcomes. Using a multi-methods approach, this study provides new evidence about how men and women use energy in rural micro-enterprises in Tanzania, and which benefits they obtain from it. In our research region, most businesses are owned by men and men-owned enterprises use electricity more frequently and intensely than women owned enterprises. The latter dominate the productive use of cooking fuels like charcoal and firewood. Electricity use is consistently associated with better business performance, but women entrepreneurs do not use it as much as men. There are multiple reasons for this gender imbalance. First, women enjoy less favourable starting conditions for enterprise creation due to poor access to finance, education, and other resources. Furthermore, women are required to balance care responsibilities with paid work and are subject to social norms that determine the acceptability of certain productive activities. Typically, female activities are less profitable and less mechanised than men's. Consequently, in the absence of gender interventions, male entrepreneurs are more likely to benefit from the promotion of productive uses of electricity. The paper discusses several approaches to improve the gender equity of PUE interventions.